2001-2002 Report on euthanasia praxis in The Netherlands: critical considerations. - Eijk, Willem J. (Medicina e Morale, 2003)
In June 2003, a third Report on the Dutch euthanasia practice has been published. The end of this investigation was to see whether medical doctors respect the regulations regarding euthanasia. From 1998 all cases of euthanasia and assisted suicide have to be reported by physicians to Regional Commissions for the Review of Euthanasia. This procedure has been maintained in the "Law for the Review of Termination of Life at Request and of Assisted Suicide" (2001), which implies that euthanasia and medically assisted suicide are legal, provided that the physician has respected a number of requirements of due care. One of these requirements is that the medical doctor reports cases of euthanasia and assisted suicide. It appears that, though the percentage of reported cases of euthanasia and assisted suicide has increased from 41% in 1995 to 54% in 2001, the total number of cases reported tends to decrease from 2000. The number of cases of termination of life without a request has remained unchanged in 2001/2002. Because medical doctors do hardly report these cases, the social control of it is impossible. Many cases of intentional termination of life are concealed as cases of terminal sedation. Moreover, it is the question whether the 13% of deaths in which a therapy has not been continued or started with the explicit intention of accelerating death, is not ethically equivalent to intentional termination of life. Therefore, the euthanasia praxis in Holland does not appear to be transparent, whereas this was the end of legalizing it. A significant fact is that the introduction of palliative care (PC) in Holland took place quite lately (during the second part of the nineties of XX century), the introduction of euthanasia on the other hand early (during the seventies). Medical doctors who function as consultants in euthanasia cases, have observed that the frequency of requests for euthanasia have diminished considerably after the introduction of PC. The conclusion is that the application of PC is the best guarantee of dealing carefully with the end of life and an antidote against euthanasia on demand.